Economization of discourse on education and pedagogization of economic problems: media debate on higher education reform in Poland. Issue 1 (2nd January 2022) - Ostrowicka, Helena
ABSTRACT: The article presents results of research into the media debate on education in the context of higher education reform in Poland. The body of press materials comprised 884 texts. The theoretical basis included critical and post-Foucauldian discourse analysis. The study revealed five themes: (1) mechanisms of economic thematization; (2) expanding the narrative of the threat to education; (3) retention of 'factories of the unemployed' discourse; (4) recruiting the voice of entrepreneurs; (5) ontological work of the 'copular' metaphor that education is economics . Potentially contradictory logics of pedagogization and economization of discourse were publicly identified and consolidated toward integration of discursive strategies and semiotic reworking of the crisis in higher education.